Revisiting the Implementation of Individual Transition Program into Workplace for Students with Intellectual Disabilities: A Brief Report from an Action Research Study - Sage, Normalia; Savira, Siti Ina (The Center for Disability Studies and Services Brawijaya University, 2024)
Research shows that success rate of post-school outcomes is lower in students with disabilities. Providing an effective transition program at schools remains a challenge. The purpose of this study is to investigate the implementation of individual transition program into workplace for students with intellectual disability. This research is qualitative research with research action method. The research was conducted at SMA Muhammadiyah 10 Surabaya which is one of the inclusion schools that consistently implements transition programs for students with disabilities. The research data was collected through interview and observation to students with intellectual disability, special education teacher, workplace and parent surrounding their experiences in internship program. The results of the study based on thematic analysis found three major themes, namely self-determination, soft-skill, and environmental factors. The study concluded that personal and environmental factors are interrelated and serve as supporting factor to one another.